Assessment of Heavy Metal Contamination and Associated Health Risks in Drugs Administered to Newborns in Iraq - Ban Hussein Ali; Abojassim, Ali (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
In this research, heavy metals such as lead (Pb), cadmium (Cd), and chromium (Cr) were determined in two types of drug samples, namely syrups and injections that were administered to newborns in Iraqi hospitals, during 2024. 30 samples of drugs were collected to investigate heavy metals using a Shimadzu AA-7000 atomic absorption spectrometer (AAS). The current study used the US Environmental Protection Agency model to calculate the carcinogen and non-carcinogen risk criteria for heavy metals in all medical samples. The average values of Pb, Cd, and Cr in syrup drug samples were 1.65 ± 0.47 mg/L, 0.34 ± 0.06 mg/L, and 1.17 ± 0.09mg/L, respectively. For injection drug samples, the corresponding average concentrations were 1.71 ± 0.45 mg/L, 0.45 ± 0.04 mg/L, and 1.26 ± 0.04 mg/L, respectively. All measured values of the concentrations of Pb, Cd, and Cr in syrup drug and injection drug were within international permissible limits; though, some injection samples showed elevated Pb levels. However, the TNCR and TCCR results for all samples were within the globally recommended limits by the US Environmental Protection Agency. Although measured concentrations of Pb, Cd, and Cr were within international permissible limits, carcinogenic and non-carcinogenic risk assessments indicate the need for continued monitoring of neonatal drugs, particularly those with elevated Pb levels.